"THE MUSIC OF CENTRAL AFRICA" by ROSE BRANDEL. Martinus Nijhoff. The Hague. 1961, XII and 272 pp. with 135 pp. of musical examples. - Kubik, Gerhard (International Library of African Music, 1962)
pages: 116-118
Keywords: African Music